The law in The Brothers Karamazov - Zolezzi Ibárcena, Lorenzo (2015)
The Brothers Karamazov was the last novel of Dostoievski and for that reason is in way a sort of synthesis of his thinking. In the article there is a brief development of some key ideas as these: in matter of guilt, the attitude has more importance than action; everyone is guilty of everything before the eyes of everyone (universal guilt); suffering purifies the individual and acts as a remedy that promotes his spiritual elevation; freewill is central in human existence. But the novel is also a novel about a crime. Somebody is murdered and the readers will discover the perpetrator at the very end. 25% of the novel is devoted to technical legal matters: the instruction of the summary and the court trial. But what is most interesting is that an innocent is found guilty, because law had no other choice having into account the facts that are backed by evidence. It would be possible to find him not guilty, but for doing so it would be necessary to change the paradigm that is the backbone of modern criminal law.